Association of the serum-free T3 and T4 hormones in severe traumatic injury - Ajagallay, Sarita; Mane, Shobita K.; Singh, Gambheer (International Surgery Journal, 2018)
Background: The main objective of the current study to investigate that the association of serum-free t3 and t4 hormones in the patient with a severe traumatic injury. Methods: The study was conducted at the trauma center, the department of general surgery, Pt. J.N.M. Medical College and associated Dr. B.R. Ambedkar Memorial Hospital, Raipur, C.G. Total 77 participants were concluded in the present study. The patients with head injuries, chest injury and abdominal injury who sustained their trauma within 24hrs of admission, within the age group of patients are 10-82 years were included. Retrospective observational study design applied to the present study. Results: The free thyroid hormone (ft3 and ft4) at different time interval at admission, at 24hrs and at 5th day was within normal limit. At admission ft3 mean=1.5 pmol/l (sd=0.18), after 24 hrs and 5th day mean ft3 was 1.47 pmol/l (sd= 0.14). The serum-free t4 mean value at admission, at 24hrs and after 5th day was 0.71 pmol/l (sd=0.52). Conclusions: The deranged fT4 levels have a significant association with the severity of trauma and the role of hormone level prediction of the trauma victims has important mechanisms which remain an unexplored subject. The prediction of the status ft3 level of the patients paves way for exploring the method through which these could be of clinical use for the patient’s management.